ERROR ANALYSIS IN COMPLETING STRUCTURE AND WRITTEN EXPRESSION OF TOEFL TEST - Misnawati Misnawati; Chalil As’ari (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2023)
The TOEFL test is commonly regarded as one of the requirements for comprehensive test or graduation for the students in an academic. Therefore, it is the obligation of students to fulfill these requirements and must to prepare more intensively to take the TOEFL test. The purpose of this research was to analyze the Structure and Written Expression of TOEFL and to investigate the underlying causes of the errors or mistakes made by the students. The subject was the students of English Department at Almuslim University. The research used mixed method. The researcher used both qualitative and quantitative designs. Data was collected through test and interviews. It can be described that the questions were consisted into three of difficulty category was 55%. While, medium category was 40% and easy category was 5% for students in answering the Structure and Written Expression. In the Structure form indicates the lowest correct answer was 11 and the highest correct answer was 73. The total the correct answer on the structure form was 235, while incorrect answer on the Structure form was 380. Whereas, in the Written Expression form the lowest answer was 45 and the highest correct answer was 92. The total correct answer on Written Expression Form was 29, while the incorrect answer on the Written Expression Form was 740. Based on research finding, it can be concluded that the students encountered similar difficulties when answering the questions in Structure and Written Expression Section of the TOEFL examination.